Inflammatory bowel disease epidemiology in São Paulo State, Brazil - Gasparini, Rodrigo Galhardi; Sassaki, Ligia Yukie [UNESP]; Saad-Hossne, Rogerio [UNESP] (Taylor & Francis, 2018)
Purpose: This study aimed to estimate the incidence and prevalence of inflammatory bowel disease (IBD) in São Paulo, Brazil, for 2012–2015. Patients and methods: This observational, descriptive, and cross-sectional study included 22,638 IBD patients out of 43,046,555 inhabitants, who had initiated their treatment through the Governmental Program of the Brazilian Unified National Health System between the years of 2012 and 2015. The onset of the disease (used to determine incidence) was established as the date of the patient’s initial registration in the Governmental Program with a diagnosis for Crohn’s disease (CD) or ulcerative colitis (UC). Every patient registered in the system as of December 2015 was included in determining the prevalence. The demographic and clinical data, such as age and sex, were collected for each patient. Statistical analysis included mean and SD, absolute and percentage frequencies, and Pearson’s chi-squared test (c²). The incidence and prevalence rates were calculated based on the estimated annual population of the State of São Paulo. Results: The study population consisted of 10,451 (46.16%) CD patients and 12,187 (53.84%) UC patients. The mean age was 42.66 (SD±16.2) years for the CD group and 47.87 (SD±16.6) years for the UC group. There was a predominance of females corresponding to 59.70% of the study population (female:male =1.48:1.00; P<0.0001). The incidence of IBD was 13.30 new cases/100,000 inhabitants per year, while the overall prevalence was 52.6 cases/100,000 inhabitants. Conclusion: This population-based study demonstrated a stability in IBD incidence rates and an increase in IBD prevalence rates in São Paulo state between 2012 and 2015. The IBD incidence and prevalence rates were comparable to European countries, with a higher occurrence in the female participants.
Keywords: Crohn’s disease; Epidemiology; Incidence; Inflammatory bowel disease; Prevalence; Ulcerative colitis